Adaptation Mechanisms of Shift Workers in Areas of the Far North - Tomus I.Yu.1, Zhilyakov E.V.1,2, Prokofieva I.Yu.1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
One uses the labor migration in various sectors of the economy. A high degree of stress on the health ofshift workers leads to rapid fatigue and the development of irreversible pathology. Within the observationof two groups during the 52-day shift, the 1st group-before the start of shift work, the 2nd group - after thecompletion of shift labor organization, one put the labor activity under study, and there was time study ofkey functions performed by workers. The body of shift workers functions with a constant level of stress inregard to regulatory adaptation mechanisms to the circumstances of the industrial and climatic environment.In the study of employees ‘ health, there was a decrease in performance at the end of the 1st month of shiftwork with confirmed Vascular and autonomic dysfunctions within the cardiointervalography. In accordancewith the cardiointervalography and measured physical strength by the method of dynamometry, there weredynamic indicators in groups at the stage of warming-up and during the completion of works. The studyof cardiointervalography revealed a negative impact of labour conditions on the cardiovascular system. Inaccordance with the results of the study, the proposals may increase the workforce productivity.